SISTEM INFORMASI PENYEWAAN TRUK BERBASIS WEB DI CV MAJU JAYA - Reza Rahim Nur; Jejen Jaenudin; Dewi Primasari (INFOTECH journal, 2024)
Information Technology is a technology that is developing rapidly at this time. Progress in every field cannot be separated from technology as its support. Problems faced by CV. Maju Jaya is the unavailability of a web-based system as a medium for truck rental which has been done by customers. The method used to create this web-based truck rental system is to use the waterfall method as one of the system development methods, modeled and documented using Context Diagram designs, Data Flow Diagrams, Entity Relationship Diagrams, and PHP as the programming language used, as well as a MySQL database as computerized data storage and transactions. The result of this research is to create a web-based truck rental system at CV. Maju Jaya to make it easier to carry out rental transactions and publish information.